Error and Mathematics Anxiety Analysis of Junior High School Students in Completing Diagnostic Tests - Soewardini, Herfa Maulina Dewi; Fuad, Yusuf; Ekawati, Rooselyna; Murdiana, Tri D. (Kreano, Jurnal Matematika Kreatif-Inovatif, 2023)
This study aims to analyze the math anxiety and wrong answers of junior high school students. As many as 11 female students and 5 male students from class VIID SMPN in Surabaya voluntarily participated in the diagnostic test during the Covid-19 pandemic. The test consists of 15 multiple choice questions and 5 description questions, carried out online with Google Meet and video on-cam, followed by structured interviews via Google Forms. The test results showed that 4 students (25%) fulfilled the KKM score and 12 students (75%) still lacked the KKM. Using the Newman error procedure, the average component of student errors was: reading (16.55%), comprehension (17.24%) ), transformation (22.07%), process skills (21.38%), and coding (22.76%) The results of the diagnosis confirmed that the factors that influence students' math anxiety are the easily nervous attitude that is routine in tests (31 .25%), nervous (37.5%), confused (56.25%), forgot the formula in multiple-choice questions (37.5%) and description questions (87.5%), and still need help from the teacher ( 37.5%), parents (75%), or peers (87.5%).Penelitian ini bertujuan menganalisis kecemasan matematika dan kesalahan jawaban dari siswa SMP. Sebanyak 11 siswa perempuan dan 5 siswa laki-laki dari kelas VIID SMPN di Surabaya secara sukarela berpartisipasi dalam tes diagnostik di masa pandemi Covid-19. Tes terdiri dari 15 soal pilihan ganda dan 5 soal uraian, dilaksanakan secara daring dengan Google meet dan video on-cam, serta dilanjutkan wawancara terstruktur melalui Google forms. Hasil tes adalah 4 siswa (25%) memenuhi skor  (KKM dan 12 siswa (75%) masih kurang dari KKM. Dengan prosedur kesalahan Newman, rerata komponen kesalahan siswa adalah: membaca (16,55%), pemahaman (17,24%), transformasi (22,07%), keterampilan proses (21,38%), dan pengkodean (22,76%). Hasil diagnosa menegaskan bahwa faktor-faktor yang mempengaruhi kecemasan matematika siswa adalah sikap mudah grogi yang rutin dalam tes (31,25%), nervous (37,5%), bingung (56,25%), lupa rumus pada soal pilihan ganda (37,5 %) maupun soal uraian (87,5%), serta masih perlu bantuan dari guru (37,5%), orangtua (75%), atau teman sebaya (87,5%).